2023
DOI: 10.1177/09564624231173024
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of gonorrhoea and chlamydia among female sex workers in northern Sydney, 2005–2019

Abstract: Background Recent reports indicate increasing gonorrhoea and chlamydia among female sex workers (FSWs) in Australia, with decreasing condom use for oral sex. Methods We determined trends in prevalence and positivity of gonorrhoea and chlamydia among FSWs attending our clinic from 2005 to 2019, by analysing data from medical and pathology records. We conducted a sensitivity analysis by using an alternative prevalence definition of first test result only per calendar year. Results Prevalence of gonorrhoea (all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…A Dutch study of 7558 FSW in 2011–2016 reported the prevalence of gonorrhoea was 1.3% at the oropharynx, 1.0% at the urogenital and 0.8% at the anorectum [24]. This is similar to a study of 3270 FSW in 2017 in Melbourne (2.0% at the oropharynx and 1.1% at the urogenital) [25], and another study of 362 FSW in 2019 in Northern Sydney (7.3% at the oropharynx, 4.5% at the urogenital and 3.3% at the anorectum) [26 ▪ ].…”
Section: Epidemiology Of Oropharyngeal Infectionssupporting
confidence: 85%
“…A Dutch study of 7558 FSW in 2011–2016 reported the prevalence of gonorrhoea was 1.3% at the oropharynx, 1.0% at the urogenital and 0.8% at the anorectum [24]. This is similar to a study of 3270 FSW in 2017 in Melbourne (2.0% at the oropharynx and 1.1% at the urogenital) [25], and another study of 362 FSW in 2019 in Northern Sydney (7.3% at the oropharynx, 4.5% at the urogenital and 3.3% at the anorectum) [26 ▪ ].…”
Section: Epidemiology Of Oropharyngeal Infectionssupporting
confidence: 85%